Stylistic Imagery: The Use Of Vehicle In Similes And Metaphors In Eunice Ngongkum’s Arrows Of Treachery And The Mbatbalung Scar - Fomukong, Seino Evangeline Agwa (Advances in Social Sciences Research Journal, 2017)
Figures of speech are imaginative tools in ordinary communications used for explaining speech beyond its usual usage. Authors use figurative language for esthetic reasons and also, to make the reader see familiar things in a new way. This is most often used in the form of analogy to convey their massage. This study analyses similes and metaphors which are the most common figures of speech in Ngongkum’s Arrows of Treachery and The Mbatbalung Scar. It aims at analysing how the images of comparison used in the vehicles add more meaning to the overall meanings of the stories. The tenor, vehicle and ground concept and the semantic field theory are used to analyse the similes and metaphors. The study concludes that the author uses vehicles that are in context, known and understood by the audience. She makes use of hyponyms of superordinate terms like faming, animals and birds, heat, geographical features and Christian references. In grouping the lexis the readers enjoy the aesthetic value and better understand the meaning of a texts.